Papyrus Prisse Line 168: Grammatical Analysis and Meaning - Kang, Seung (Zeitschrift für ägyptische Sprache und Altertumskunde, 2008)
Papyrus Prisse line 168 can be best explained as the second tense construction conveying a hypothetical sense: “Should he (= man of character) seize, he would be like a crocodile in the court of magistrates.”